2009
DOI: 10.1111/j.1365-2265.2008.03495.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism during pregnancy and the effect of rising calcium on pregnancy loss: a call for earlier intervention

Abstract: HPT during pregnancy is under recognized and is associated with a 3.5-fold increase in miscarriage rates. Pregnancy loss often occurs in the second trimester and is associated with multiple miscarriages when not addressed. Pregnancy loss is more common as calcium levels exceed 11.4 mg/dl (2.85 mmol/l), but can be seen at all elevated calcium levels. Emphasis is placed on earlier recognition and surgical cure before becoming pregnant, however, once pregnant, surgery should be offered early in the second trimest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
166
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(182 citation statements)
references
References 26 publications
7
166
0
7
Order By: Relevance
“…An association between gestational PHPT and pregnancy loss has been suggested, and so far only one study has been able to determine the rate of pregnancy loss in women with gestational PHPT (5). The study showed a 3.5 higher rate of spontaneous abortions in women with PHPT.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…An association between gestational PHPT and pregnancy loss has been suggested, and so far only one study has been able to determine the rate of pregnancy loss in women with gestational PHPT (5). The study showed a 3.5 higher rate of spontaneous abortions in women with PHPT.…”
Section: Introductionmentioning
confidence: 83%
“…The existing literature describing the consequences of gestational PHPT is limited, and mainly consists of case reports or case series (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28). In total, these studies reported 33 pregnancies in women with PHPT, who did not undergo surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, 48% of pregnancies complicated by untreated hyperparathyroidism ended in a miscarriage, which was directly related to the degree of hypercalcemia. 34 An association between maternal hypercalcemia and fetal polyhydramnios, fetal demise and neonatal hypocalcemia was shown in another retrospective case series. 35 Thus, maternal hypercalcemia should be ruled out in women with a history of unexplained fetal loss, polyhydramnios, previous neonatal hypocalcemia or severe hyperemesis.…”
Section: Discussionmentioning
confidence: 99%